Toolkit for community groups: promoting the well-being of migrants & displaced persons - Ata, Ayar; Jos, Hermans; Jamaludin, Thandar Soe@Sumaiyah; Janzing, Sigfried; Jeurgens, Charles; Mifsud, Alex; Ogbuigwe, Akpezi; Raza, Saima; Sayer, Ahmet; Wade, Rosalind; Win @ Fahmida, Nilar (2020)
This toolkit is designed for communities who are trying to promote well being and inclusion and who wish to celebrate diverse cultures and experience. Migration is not a new phenomenon. Humans have always travelled and if we look back far enough in our family histories we will find that we are all migrants. The world crisis over the COVID 19 virus has shown that there is a danger that some vulnerable communities can be sidelined or forgotten. The toolkit provides ideas and shares examples of activities which address negative perceptions and stereotypes of migrants and aims to build more positive relationships.